(3cjajI JNajV GdfabGJ aj GdTQcGJ (B/s - (3CdGf, Lhfs; (3GdYGeQj, NGdO s ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2001)
(3GdehXahf(B- (3GdGSS GdNGUI HYedjI GdTQGA(B- (3GdJehjd hGdCSge(B- (3GdEOGQI(B- (3JcfhdhLjG GdeYdheGJ(B- (3GdeHjYGJ hGdJhRjY(B- (3hVY SjGSI hGYjI HCgejI GdJhajQ aj GdfabGJ(B- (3bGFeI aMU dYedjI NaV GdfabGJ(B.s
Keywords: (3GdTQcGJs; (3GdfabGJs